Competences Of Teachers: Differentiated Learning, Solutions In Diversity - Yuyun Elizabeth Patras; Khusnul Mubarok; Gumgum Gumelar; Erry Utomo; Rais Hidayat (AL-ISHLAH: Jurnal Pendidikan, 2023)
Teachers are a central part of the education process. Without teachers, education would not run smoothly. It is the most important asset in human resource development. Therefore, teachers' competencies need to be further improved to support their professional skills. The purpose of this study is to review and describe the results of research on differentiated learning in Indonesia, especially in the context of primary education in order to find new ways for education, especially in primary education. This research uses a qualitative approach with content analysis technique. Data analysis is carried out with the stages of concept examination, examination of critical matters. Teachers as one of the main actors in the implementation of education must certainly equip themselves with different skills and competencies in accordance with the times. In the learning process, teachers must use the right learning strategy, one of which is differentiated learning. There is a new way that teachers can take in improving teacher competence in accordance with what is regulated in the Teacher and Teacher Law, namely the fulfillment of four components in differentiated learning, namely content, process, product, and learning environment, to facilitate student learning activities according to their uniqueness and diversity.